2008
DOI: 10.1128/mcb.01345-07
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Regulates Alternative Splicing in a Subset of Cancer-Associated Genes: a Role for SC35

Abstract: Alternative splicing of pre-mRNA contributes significantly to human proteomic complexity, playing a key role in development, gene expression and, when aberrant, human disease onset. Many of the factors involved in alternative splicing have been identified, but little is known about their regulation. Here we report that caffeine regulates alternative splicing of a subset of cancer-associated genes, including the tumor suppressor KLF6. This regulation is at the level of splice site selection, occurs rapidly and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 54 publications
2
43
0
Order By: Relevance
“…This is accomplished, at least in part, by the induction of high levels of SRSF2 (29). In the present report we extend our analyses by addressing the mechanism(s) that lead to increased levels of SRSF2 protein.…”
Section: Alternative Splicing (As)supporting
confidence: 60%
See 1 more Smart Citation
“…This is accomplished, at least in part, by the induction of high levels of SRSF2 (29). In the present report we extend our analyses by addressing the mechanism(s) that lead to increased levels of SRSF2 protein.…”
Section: Alternative Splicing (As)supporting
confidence: 60%
“…Real-time PCR was performed using SYBR Green PCR Master Mix (AB Applied Biosystems/ Life Technologies) and individually designed primer sets. For total SRSF2 mRNA, sense: 5Ј-CTG AGG ACG CTA TGG ATG CCA-3Ј and antisense: 5Ј-GAC TTG GAC TTG GAC CTT CGT-3Ј; for ␤ 2 M, the same as previously reported (29); for FLAG-SRSF2, sense: 5Ј-CGA CTC ACT ATA GGG AGA CC-3Ј and antisense: 5Ј-GAG GTG CGG TAG GTC AGG TT-3Ј; for GFP, sense: 5Ј-GGG TGA AGG TGA TGC AAC ATA C-3Ј and antisense: 5Ј-CTC GCA AAG CAT TGA ACA CCA-3Ј. The final C t value was an average of 3 repeats of each assay, repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…Accessing PUPASUITE web we observed that the polymorphic allele (A) disrupts the binding sites for the SR proteins SC35, SF2 and SRp40 (nucleolar, serine-rich protein). Overexpression of SRp40 was found during mouse mammary tumorigenesis; aberrant increases in SC35 have been associated with the cancer phenotype and SF2/ASF has been recently identified as a proto-oncogene [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…SFRS2 or SC35 is another splicing factor with role in the alternative splicing of the tumor suppressor gene KLF6. 32 This splicing factor is also a transcriptional target of E2F1 and shown to change splice profiles of various apoptotic genes. 33 These data support the notion that alterations of splicing factors contribute to oncogenesis.…”
Section: Discussionmentioning
confidence: 99%